Narrative review of contemporary treatment options in the care of patients with obstructive sleep apnoea. (November 2017) - Ferguson, Mark S.; Magill, Jennifer Claire; Kotecha, Bhik T.
Snoring and obstructive sleep apnoea (OSA) are increasingly common conditions, and confer a significant health and socioeconomic burden. Furthermore, untreated OSA represents a significant mortality risk. Patients require careful assessment, including detailed clinical history and examination, sleep study and drug-induced sleep endoscopy (DISE). Although nasal continuous positive airway pressure (nCPAP) is the gold standard treatment for moderate and severe OSA, multidisciplinary team assessment is often required to develop the best treatment plan for an individual, especially when nasal CPAP is poorly tolerated. There is a wide range of medical and surgical treatment options, and following appropriate patient selection and assessment, a focused site-specific, often multilevel, intervention is indicated. There is an increasing body of evidence in the literature supporting these multilevel interventions and with agreement on standardized outcome measures more trials are likely to improve the robustness of these data further.